Perancangan Ulang Tata Letak Untuk Pengoptimalisasian Ruang Pada Toko Ritel 3D Mart Sukabumi - Ramadhani, Alda Puspita; Azzahra, Andiny; Indah, Diva Aprilia Nur; Gunawan, Sinta; Husyairi, Khoirul Aziz; Ainun, Tina Nur (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Effective store layout planning is crucial for long-term business success. 3D Mart Sukabumi faces challenges with inefficient shelf and basket placement, hindering customer navigation and leading to product loss. This research aims to address these issues by employing Total Closeness Rating (TCR) and Activity Relationship Chart (ARC) methods to analyze facility relationships and design a layout that optimizes material flow and minimizes distances. The proposed layout solution rearranges the placement of shopping baskets. The TCR calculations indicate that display racks (TCR: 384) are ranked first in importance, followed by the warehouse (TCR: 327). The overall goal is to redesign 3D Mart's store layout to enhance product placement, space utilization, sales, customer experience, and overall profitability.